2018
DOI: 10.1002/chem.201706072
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Aza‐Michael Addition of the Flavonoid (+)‐Taxifolin in the Inhibition of β‐Amyloid Fibril Aggregation

Abstract: Inhibition of abnormal protein self-aggregation is an attractive strategy against amyloidogenic diseases, but has found limited success due to the complexity of protein self-assembly, the absence of fully reproducible aggregation assays, and the scarce knowledge of the inhibition mechanisms by small molecules. In this context, catechol-containing compounds may lead to covalent adducts with amyloid fibrils that interfere with the aggregation process. In particular, the covalent adduct formed between the oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 82 publications
3
10
0
Order By: Relevance
“…Unlike most conjugate addition reactions, the initial ratedetermining step is endothermic probably due to steric interactions of the bulky grandifloracin structure with the tripeptide, which means that steric accessibility of the reactant could be a major driving force for the feasibility of the reaction. A similar finding was also observed with the addition of Lys16 (of β-amyloid Aβ42 fibrils) to oxidized (+)-taxifolin [65], wherein the formation of the enol adduct is endothermic.…”
Section: Binding Free Energy Calculationssupporting
confidence: 76%
“…Unlike most conjugate addition reactions, the initial ratedetermining step is endothermic probably due to steric interactions of the bulky grandifloracin structure with the tripeptide, which means that steric accessibility of the reactant could be a major driving force for the feasibility of the reaction. A similar finding was also observed with the addition of Lys16 (of β-amyloid Aβ42 fibrils) to oxidized (+)-taxifolin [65], wherein the formation of the enol adduct is endothermic.…”
Section: Binding Free Energy Calculationssupporting
confidence: 76%
“…[14] This was confirmed by a computational study analyzing the reaction mechanism. The covalent adduct is formed via an aza-Michael addition of the oxidized o -quinone species of (+)-taxifolin with a lysine residue of the A β 42 fibril [15]. Previously, taxifolin was semisynthetically esterified in position 7 with gallic acid by Vrba et al and shown to upregulate the nuclear factor (erythroid-derived 2)-like 2 (Nrf2) pathway in RAW264.7 cells [16], an important cytoprotective mechanism in response to redox imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…[31] The choice of 8c was motivated by the presence of the nitro group, which would helpt os tabilizet he binding mode throughe lectrostatic interactions with the protonated amino group of K16 residues along the binding groove.T his would enhancet he residence time aroundt he reactive site and facilitate the propera rrangement for covalenta dduct formation,a s described for the aza-Michaela ddition observed for taxifolin. [32] However,n one of the three simulated poses for compound 8c were able to maintain ap ropero rientation around the reactive site delimited by K16 and D22 in the bindingg roove (cf. distances d1a nd d2i nF igure S1 in the SupportingI nformation).…”
Section: Formation Of Covalent Adducts With Ab42 Fibrilsmentioning
confidence: 99%
“…[30] Protonation states for the protein were set at pH 7.4. According to previous pK a studies, [32] one K16 located in the middle of the fibril assembly was simulated in its neutral form. For each of the six tested compounds, the oxidized o-quinone form was generated and used during docking.…”
Section: Docking and MD Simulations Of Complexes With Ab42 Fibrilsmentioning
confidence: 99%